Pendampingan Bahasa Inggris Komunikasi Kepada Anak-Anak di Panti Asuhan Yayasan Dharma Jati II Denpasar, Bali: Mentoring English Communication to Children at the Dharma Jati II Foundation Orphanage in Denpasar, Bali - Kadek Ayu Ekasani; Ni Made Ayu Natih Widhiarini; I Gede Made Aditya Agastia (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Community service activities at the Dharma Jati II Orphanage are communicative English language assistance that emphasizes speaking skills. The problem that arises in partners is that there is no English language training and development provided by the orphanage. The desire of the orphanage administrators in improving children's English skills, especially in speaking, is very large considering the importance of mastering English as an international language in this era of globalization. The purpose of this community service is to provide English language assistance to orphanage children so that they are able to improve their English skills, especially in speaking. The method used goes through three stages, namely the preparation stage, the implementation stage, and the evaluation stage. The results obtained from the assistance are a good method to use is role playing with occasionally slipping games that are fun for the orphanage children. In the future, this activity will be carried out more often to help orphanage children improve their English language skills, not only speaking skills, but also in 3 other English language skills, such as reading, writing, and listening.